SQ-DM: Accelerating Diffusion Models with Aggressive Quantization and Temporal Sparsity - Fan, Zichen; Dai, Steve; Venkatesan, Rangharajan; Sylvester, Dennis; Khailany, Brucek (2025 62nd ACM/IEEE Design Automation Conference (DAC), 2025)
Diffusion models have gained significant popularity in image generation tasks. However, generating high-quality content remains notably slow because it requires running model inference over many time steps. To accelerate these models, we propose to aggressively quantize both weights and activations, while simultaneously promoting significant activation sparsity. We further observe that the stated sparsity pattern varies among different channels and evolves across time steps. To support this quantization and sparsity scheme, we present a novel diffusion model accelerator featuring a heterogeneous mixed-precision dense-sparse architecture, channel-last address mapping, and a time-step-aware sparsity detector for efficient handling of the sparsity pattern. Our 4-bit quantization technique demonstrates superior generation quality compared to existing 4-bit methods. Our custom accelerator achieves 6.91 × speed-up and 51.5% energy reduction compared to traditional dense accelerators.